A study of relationship between organization justice and organization citizenship behaviour among non- officer workers in local government / Ahmad Shahir Abdullah - Abdullah, Ahmad Shahir (Faculty of Business and Management, 2011)
Organization Citizenship Behavior plays an important role in determining the successfulness of an organization. Organizations around the world face similar business challenges such as the difficulty to manage the employee especially the non-executive workers. If the employees are well-behaved, the level of fairness and motivation will be high and therefore, it will influence the organization’s performance resulting in higher productivity and simultaneously bring into organizational successfulness. When looking at this problem area, we found that there might be actions that companies can use to cater to this problem in reducing the employee’s deviant behavior. The past researcher shows that there have many factors that affect the organization citizenship behavior which one of it is organization justice. This study will focus on three factors that could affect employee’s behavior which is distributive justice, procedural justice and interactional justice. If the employee are well behaved, the level of fairness’ and motivation will be high and therefore, it will influence the organization performance resulting in higher productivity in organization successful.